The influence of iconic material on the evaluation of an utterance - Wszołek, Mariusz; Siemes, Annette; Fleischer, Michael (Papers in Linguistics, 2025)
The article presents the results of research inspired by an experiment published in the Psychology Development journal in the article “Stable Truthiness Effect Across the Lifespan,” examining the truthiness effect based on photographic material. The subject of the presented study is how communication offers interact at the verbal and visual levels, and whether and to what extent the linkability of oral utterances differs from that of utterances using two channels of reception (verbal and visual). In the study, the respondents were asked to fill in a questionnaire containing 21 statements, with a request to evaluate them in terms of true or false. The study was conducted in two stages: first, presenting only the text of the statement, and the other time, the text with a photo placed above it. The data obtained empirically show that the photo next to a given statement does not affect the respondent’ rejection or acceptance of the information.